Morphology and Adaptation Features of the Slang Suffixal Adverbs in Lithuanian Language: Hybrid Derivatives of Suffix -ai from Suffixal Adjectives of Russian - Kudirka, Robertas (Respectus Philologicus, 2019)
This article analyses 127 suffixal adverbs from Lithuanian slang and non-standard dictionary (Kaunas, 2012). The suffixal adverbs of Lithuanian slang have not been researched systematically according to grammatical classification. This research is based on the morphological analysis. The suffixal adverbs are divided into groups: every group includes some subgroups. First, the most productive derivatives groups are analyzed, then the less productive groups are involved. In each subgroup are described derivatives of individual suffixes; where necessary, due consideration is given to the underlying structure and various morphological properties. Every subgroup has a small description of the accentuation and the pronunciation or the root vocalism.